MnO2 nanosheets based fluorescent sensing platform with organic dyes as a probe with excellent analytical properties1. Issue 12 (21st June 2015) - Wang, Chunxia; Zhai, Wanying; Wang, Yuexiang; Yu, Ping; Mao, Lanqun
<x xml:space="preserve">Abstract</x> A novel strategy to use organic dyes, instead of emissive nanoparticles, as the probe to construct a biosensing platform based on manganese dioxide (MnO2) nanosheets with excellent analytical properties is developed.